Presupposition Analysis in Instagram Captions of L’oreal Paris Colorsonic Hair-Coloring Device Advertisement - Nadia Janice Tanjaya (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
This study analyzes the types of presuppositions and the messages they convey in Instagram captions of L’Oréal Paris Colorsonic Hair-Coloring Device advertisements posted between June 2024 and June 2025. Presupposition refers to assumptions that writers or speakers believe the audience have already known, and it plays an important role in influencing how messages are understood. A total data of twenty-four captions from L’Oréal Paris’s official Instagram account were collected. Using a qualitative approach and Yule’s theory (1996, 2010) the data were analyzed. The findings found five types of presuppositions: existential, lexical, structural, factive, and counterfactual. Existential presupposition appeared the most frequently, followed by lexical and structural presuppositions. Factive and counterfactual presuppositions appeared less often, while non-factive presuppositions were not found. The results show that presuppositions make the product as familiar, trustworthy, and emotionally appealing to the audience. This is done by implying ideas of confidence, beauty, and innovation. In conclusion, presupposition works as an effective strategy because it delivers hidden messages, such as suggesting the product’s quality or benefits, without stating them directly.